Suicide While Locked Up in Texas: Risk Factors for Death by Suicide in Custody - Marks, Rocky B. (Journal of interpersonal violence, 2024)
In the United States, suicide is a leading cause of death in prisons and jails, with incarcerated individuals being nine times more likely to die by suicide than the general population. Identifying vulnerabilities at each stage of custody (prebooking, jail, prison) and factors that increase suicide risk can improve prevention efforts. A hierarchical binary logistic regression was conducted on data from the Texas Justice Initiative’s Deaths in Custody Report. Variables included race/ethnicity, sex, age at death, days in custody, classification of crime as violent or nonviolent, and custody type of prebooking, jail, or prison. Among main effects, when compared to suicide rates in prison, jail suicide deaths were over three and a half times more likely (OR = 3.61), and the period of prebooking emerged as a period of staggering risk of suicide death, with suicides being over 5,000% more likely than at other stages of custody (OR = 50.86). When interactions were entered, Latinx individuals were at a particularly increased risk of suicide death (OR = 10.46), likelihood of suicide death decreased with each year of age (OR = .89), nonviolent offenders were just under three and a half times more likely to die by suicide when compared to violent offenders (OR = 3.45), and each stage of custody was shown to affect the relationship between age-related rates of suicide in different ways. Results call for further investigation into suicide among understudied populations in corrections, such as Latinx individuals, juveniles in the prison system, and nonviolent offenders, to identify the groups at the highest risk of premature death in correctional systems.